Discordance in activated partial thromboplastin time and anti-factor Xa levels in COVID-19 patients on heparin therapy - Lawlor, Matthew (Thromb Res, 2021)
• aPTT correlates poorly with anti-Xa in COVID-19 patients receiving unfractionated heparin. • aPTT potentially underestimates heparin activity compared with anti-Xa in COVID-19 patients receiving unfractionated heparin. • Elevated fibrinogen levels did not correlate with refractory aPTT in COVID-19 patients.